Modeling and experimental investigation of quasi-zero stiffness vibration isolator using shape memory alloy springs - Xuerong Hu; Yuxiang Han; Junyan Lu; Linxiang Wang (Electronic Research Archive)
Low-frequency vibration isolation is an attractive research topic in vibration control. In this study, a novel quasi-zero stiffness isolator utilizing shape memory alloy (SMA) springs is proposed. Leveraging the inherent stress plateau characteristics caused by the super-elastic effect of SMA, this design significantly improves the isolation performance at low-frequency excitations. We began by reformulating the static constitutive equation of the SMA spring, and the torsional strain of the spring was taken into account into the static constitutive equation. Subsequently, the dynamics of the SMA spring was modeled as an ordinary differential equation using the Euler-Lagrange equation. The SMA spring was fabricated and tensile tests were performed to validate the model given by dynamic differential function. Building on the validated spring model, a dynamic model of the quasi-zero stiffness isolator using SMA springs was proposed and its response under sinusoidal excitation was analyzed. The amplitude-frequency response of the system was determined using the harmonic balance method (HBM), and superior performance of the isolator in attenuating low-frequency vibrations was confirmed. Finally, an experimental platform was constructed to evaluate the isolator's performance under low-frequency excitations at 0.5, 1.0, 1.5, and 2.5 Hz. Our results demonstrated the effectiveness of the proposed quasi-zero stiffness vibration isolator system in isolating low-frequency vibrations, and the simulation results were verified by the experimental counterparts.